Implementation Of The One-Stop Integrated Service (PTSP) In Enhancing Public Service Quality At The Probolinggo District Court - Siti Marwiyah; Eko Yudianto; Muchammad Teguh Firmansyah (The Future of Education Journal, 2026)
The One-Stop Integrated Service (PTSP) is an administrative service innovation introduced within the judicial sector to enhance service quality, simplify public access, and improve user satisfaction. This study aims to examine the implementation of the One-Stop Integrated Service and its influence on the quality of public services at the Probolinggo District Court. A descriptive qualitative approach was employed in this research. Data were collected through observations, interviews, and documentation, while the analysis followed an interactive model consisting of data reduction, data display, and conclusion drawing. The study adopted the policy implementation framework developed by Van Meter and Van Horn, which emphasizes policy standards and objectives, resources, characteristics of implementing agencies, inter-organizational communication, implementers’ disposition, and socio-economic and political conditions. The findings indicate that the implementation of PTSP at the Probolinggo District Court has been carried out effectively and has contributed to improving public service quality. This improvement is reflected in easier access to services, clearer administrative procedures, greater efficiency and effectiveness in service delivery, and the availability of supporting facilities and infrastructure. Nevertheless, several challenges remain, including limited human resources during peak service periods and the increasing number of service users, which requires adjustments in service capacity. Therefore, continuous efforts are needed to strengthen staff competencies, optimize the use of information technology, and enhance service management systems to achieve more responsive, transparent, and high-quality public services.